Assessment of sleep quality and sleep disordered breathing among post-hospitalized patients with COVID-19 - Castellanos, Paula L.; Satashia, Parthkumar; Punj, Mantavya; Castillo, Pablo R.; Colaco, Brendon M.; Dredla, Brynn K.; Festic, Emir; Kaplan, Joseph; Ruoff, Chad M.; Speicher, Leigh L.; Walsh, Katherine L.; Werninck, Natalia; et al. (Frontiers in Sleep, 2023)
We conducted a cross-sectional study to identify the presence of sleep disturbance and sleep disordered breathing in post-hospitalized patients with COVID-19 compared to a cohort of patients with no prior COVID-19 infection.Patients who were discharged from Mayo Clinic after hospitalization for COVID-19 and who had no existing diagnosis of sleep apnea or other sleep disorders were recruited for this study as cases. Patients who never had COVID-19 infection, nor any existing diagnosis of sleep apnea or other sleep disorders, were recruited from outpatient clinics as controls. Participants completed Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, and Fatigue Severity Scale questionnaires, as well as a home sleep apnea test.Forty-seven COVID-19 cases and 46 controls completed questionnaires. Cases were significantly older, with a median age of 56.0 vs controls (50.5) and were found to have slightly worse sleep quality, a higher degree of daytime sleepiness, and a slightly higher degree of fatigue. In terms of sleep disordered breathing, 39 cases and 40 controls completed the home sleep apnea test. Obstructive sleep apnea, defined by an AHI score of 5 or higher, was found in a remarkable 97.4% of cases vs 72.5% in controls. Severity of OSA also trended higher in the case group. However, the difference in AHI was not significant after adjusting for age and BMI.Patients who were hospitalized with COVID-19 showed a very high prevalence of OSA. In addition, they had a slightly higher degree of sleep disturbance, daytime sleepiness, and fatigue when compared to controls. Our results suggest that sleep medicine assessment in patients who had COVID-19 requiring hospitalization is warranted.